Dental biofilm infections – an update. Issue 4 (April 2017) - Larsen, Tove; Fiehn, Nils‐Erik
Abstract : Teeth are colonized by oral bacteria from saliva containing more than 700 different bacterial species. If removed regularly, the dental biofilm mainly comprises oral streptococci and is regarded as resident microflora. But if left undisturbed, a complex biofilm containing up to 100 bacterial species at a site will build up and may eventually cause development of disease. Depending on local ecological factors, the composition of the dental biofilm may vary considerably. With access to excess carbohydrates, the dental biofilm will be dominated by mainly gram‐positive carbohydrate‐fermenting bacteria causing demineralization of teeth, dental caries, which may further lead to inflammation and necrosis in the pulp and periapical region, i.e., pulpitis and periapical periodontitis. In supra‐ and subgingival biofilms, predominantly gram‐negative, anaerobic proteolytic bacteria will colonize and cause gingival inflammation and breakdown of supporting periodontal fibers and bone and ultimately tooth loss, i.e., gingivitis, chronic or aggressive periodontitis, and around dental implants, peri‐implantitis. Furthermore, bacteria from the dental biofilm may spread to other parts of the body by bacteremia and cause systemic disease. Basically, prevention and treatment of dental biofilm infections are achieved by regular personal and professional removal of the dental biofilm.